2020
DOI: 10.3390/biom10060818
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Biological Screening of Oenothera biennis L. Hydroalcoholic Extract

Abstract: Oenothera biennis L. (OB), also commonly known as evening primrose, belongs to the Onagraceae family and has the best studied biological activity of all the members in the family. In therapy, the most frequently used type of extracts are from the aerial part, which are the fatty oils obtained from the seeds and have a wide range of medicinal properties. The aim of this study was to evaluate the phytochemical composition and biological activity of OB hydroalcoholic extract and to provide directions for the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…It has been revealed that the extract of aerial parts of O. biennis inhibited the migration abilities of human melanoma cell lines A375 in a concentration-dependent manner [ 56 ]. In contrast, oral supplementation of oil from evening primrose (EPO) favors skin regeneration via increasing wound healing properties in dermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that the extract of aerial parts of O. biennis inhibited the migration abilities of human melanoma cell lines A375 in a concentration-dependent manner [ 56 ]. In contrast, oral supplementation of oil from evening primrose (EPO) favors skin regeneration via increasing wound healing properties in dermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Granica et al [ 31 ] investigated and identified 39 polyphenols from 50% ethanol extracts of the aerial parts of OB with UHPLC fingerprinting and tandem mass spectrometry analyses. In addition, Fecker et al [ 32 ] recently found, by HPLC-UV analysis, that a 70% ethanol extract of the aerial parts of OB contained gallic acid, caffeic acid, epicatechin, coumaric acid, ferulic acid, rutin and rosmarinic acid. Wang et al [ 33 ] isolated the ethyl acetate fraction from a 50% methanol extract of OB seed and identified gallic acid, procyanidin B3, catechin, and methyl gallate, along with aldose reductase inhibitory activity, using HPLC fingerprinting and proton NMR microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine extract of OB sprouts can scavenge DPPH radicals and inhibit the production of pro-inflammatory mediators in lipopolysaccharide-(LPS-) treated macrophages [29,30]. Methanol extract of aerial parts of OB can inhibit ROS production in neutrophils and demonstrates anti-inflammatory activity via the suppression of hyaluronidase and lipoxygenase [31]. e representative compounds in the extract of OB aerial parts were reported to be a part of flavonoid glycosides, such as kampherol-3-O-glucoside, quercetin-3-O-galactoside, quercetine-3-Orhamnoside and myricetin-3-O-glucoside, phenolic acids, and tannins [32].…”
Section: Discussionmentioning
confidence: 99%